2019
DOI: 10.1177/2150132719867587
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility Pilot Outcomes of a Mammography Decision Support and Navigation Intervention for Women With Serious Mental Illness Living in Supportive Housing Settings

Abstract: Objective: People with serious mental illness (SMI) experience significant disparities in morbidity and mortality from preventable and treatable medical conditions. Women with SMI have low mammography screening rates. SMI, poverty, and poor access to care can have a significant effect on a woman’s opportunity to learn about and discuss breast cancer screening with health care providers. This study examines the feasibility pilot outcomes of mammography decision support and patient navigation intervention (DSNI)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…The identified barriers, such as hepatitis B stigma, HCC taboo and social norms of enduring hardship, provide new insights for future inspections in other regions. Second, the study also mapped findings based on the PHM, which has been effectively verified in different cultures to predict cancer screening utilisation and may increase the generalisability of the current findings (Weinstein et al, 2019).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…The identified barriers, such as hepatitis B stigma, HCC taboo and social norms of enduring hardship, provide new insights for future inspections in other regions. Second, the study also mapped findings based on the PHM, which has been effectively verified in different cultures to predict cancer screening utilisation and may increase the generalisability of the current findings (Weinstein et al, 2019).…”
Section: Discussionmentioning
confidence: 98%
“…• Insights have important implications for diminishing the global burden of hepatocellular carcinoma from late diagnosis, and progress towards the World Health Assembly endorsed global hepatitis targets for improving survival in hepatitis B. fatalism and stigma) and sociostructural (limited health resources) levels for breast, cervical and colorectal cancer (Huhmann, 2020;Weinstein et al, 2019). Conversely, HCC screening targets a population with chronic diseases and the liver ultrasound screening modality is more accepted than the colonoscopy, mammography and the Papanicolaou test, which have an invasive or sensitive nature (Omata et al, 2017).…”
Section: What Does This Paper Contribute To the Wider Global Clinical...mentioning
confidence: 99%
See 2 more Smart Citations
“…A previous meta‐analysis showed that patient navigation was effective for increasing cancer screening rates among populations adversely affected by healthcare disparities, although people with severe mental illness were not included in this previous research 26 . In a study of patient navigation to encourage participation in breast cancer screening, Weinstein et al reported preliminary efficacy for women with serious mental illness living in a supportive housing setting 27 . Given that the present randomized controlled trial confirmed efficacy among people with schizophrenia, patient navigation may be an important component of the intervention to encourage participation in cancer screening.…”
Section: Discussionmentioning
confidence: 98%